2004
DOI: 10.1158/1078-0432.ccr-0731-03
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Overexpression of Cyclooxygenase-2 in HER-2–Positive on Smad4-Reduced Human Gastric Carcinomas Is Associated with a Poor Patient Outcome

Abstract: Purpose: The expression of cyclooxygenase-2 (COX-2) is known to be involved in gastric carcinogenesis and tumor progression, but little is known about the mechanisms responsible for the up-regulation of COX-2. We examined the involvement of two growth factor-signaling systems, HER-2 and transforming growth factor (TGF)-␤, in the induction of COX-2 in human gastric cancer tissue.Experimental Design: COX-2 expression was detected by immunohistochemistry in surgical specimens obtained from 166 patients with advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 39 publications
1
9
0
2
Order By: Relevance
“…A number of studies have previously shown COX-2 expression to correlate with clinicopathologic variables in gastric cancer, such as depth of tumor invasion, size, lymph node metastasis, stage, and microvessel density (26 -37), but the association of COX-2 with survival has been controversial. Several groups have reported no correlation with survival (30, 32, 38, 39) whereas others have described COX-2 to correlate with survival, but in a nonindependent manner (28,37) or in patients with an advanced disease (36). However, Shi et al (35) have reported that COX-2 is an independent prognostic factor in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have previously shown COX-2 expression to correlate with clinicopathologic variables in gastric cancer, such as depth of tumor invasion, size, lymph node metastasis, stage, and microvessel density (26 -37), but the association of COX-2 with survival has been controversial. Several groups have reported no correlation with survival (30, 32, 38, 39) whereas others have described COX-2 to correlate with survival, but in a nonindependent manner (28,37) or in patients with an advanced disease (36). However, Shi et al (35) have reported that COX-2 is an independent prognostic factor in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Functional complementation of impaired TGF-b signalling occurred in BIC-1 cells when Smad4 expression was re-established ( fig 9). smad4 was first identified as a candidate tumour suppressor in pancreatic cancer, 8 and since then mutations have been detected in one third of metastatic colorectal cancers, 9 27 two thirds of gastric carcinomas, 28 and recently a complex pattern of mutations and abnormal splicing of Smad4 has been demonstrated in thyroid tumours. 29 Furthermore, mice heterozygous for smad4 develop gastric polyps months after birth that progress to invasive carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer we and others have shown that COX-2 expression is associated with intestinal histological subtype, proximal location, large tumor size, and advanced stage [27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Association of COX-2 with survival has been controversial, since some studies show no such link [32][33][34].…”
Section: Cox-in Human Gastric Carcinogenesismentioning
confidence: 99%